1995
DOI: 10.1111/j.1365-2796.1995.tb01229.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological mechanisms in atherosclerosis

Abstract: . Immunological mechanisms seem to be potent modulators of the atherosclerotic process. The presence of substantial numbers of T‐lymphocytes in the lesion and local and circulating autoantibodies to plaque components suggests that a specific immune response is operating. Focal expression of adhesion molecules and local secretion of chemoattractants could mediate the recruitment of inflammatory cells to the lesion. Local cytokine and growth factor networks may operate later, controlling cell migration and prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 89 publications
0
31
0
Order By: Relevance
“…In recent decades, many reports have described a significant elevation of LPC levels in cells and tissues in different diseases (9,32,41). Numerous lines of evidence suggest that LPC, which is a major lipid component of oxidized low density lipoprotein, and which accumulates in atherosclerotic lesions (11), plays pathological roles in the development of atherosclerosis and other chronic inflammatory diseases (11,12). LPC also plays other important biological roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, many reports have described a significant elevation of LPC levels in cells and tissues in different diseases (9,32,41). Numerous lines of evidence suggest that LPC, which is a major lipid component of oxidized low density lipoprotein, and which accumulates in atherosclerotic lesions (11), plays pathological roles in the development of atherosclerosis and other chronic inflammatory diseases (11,12). LPC also plays other important biological roles.…”
Section: Discussionmentioning
confidence: 99%
“…LPC is an important lipid mediator involved in many cellular processes. In particular, LPC is believed to play an important role in atherosclerosis and inflammatory diseases by altering various functions of a variety of cell types, including endothelial cells, smooth muscle cells, monocytes, macrophages, and T cells (11)(12)(13). However, the reported signaling mechanisms of LPC are variable and the initial interaction of LPC with cell membranes is poorly understood.…”
Section: Spcmentioning
confidence: 99%
“…Secondly, a localised inflammatory response associated with atherosclerosis, with cytokine production by all cells involved in the atherosclerotic plaque [41], may induce a systemic acute-phase response. A 'haematological stress syndrome' in non-diabetic subjects with atherosclerosis was recognised more than a decade ago [48], and recent studies confirm an association between acute-phase indices such as C-reactive protein and sialic acid and CHD in the normal population [49].…”
Section: Discussionmentioning
confidence: 99%
“…As well as affecting hepatic protein synthesis, lipoprotein metabolism [40] and the hypothalamic pituitary axis, TNFa, IL-1 and -6 contribute to atherogenesis in several other ways such as by inducing adhesion molecules, stimulating smooth muscle proliferation and increasi n g endothelial permeability [41]. TNFa, a potent inhibitor of the tyrosine kinase activity of the insulin receptor, is being investigated as a mediator of insulin resistance in obesity and NIDDM [42].…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of Type II diabetic subjects from a diabetic clinic (the Guy's-Lewisham Diabetes Survey), we found that there was a strong univariate association in men between high serum sialic acid concentrations and coronary heart disease [26]. Apart from the acute-phase proteins which are established or putative risk factors for cardiovascular disease such as fibrinogen, serum amyloid A, PAI-1, Lp(a) lipoprotein and VLDL triglyceride, proinflammatory cytokines produced at the sites of diabetic complications or by the diabetic process itself (see below) may also exacerbate atherosclerosis by acting on the endothelium, smooth muscle cells and macrophages [57]. We found that women with Type II diabetes who lose the protection from cardiovascular disease enjoyed by nondiabetic women and who possibly have a higher risk of this disease than men with Type II diabetes, have a higher serum sialic acid concentration than Type II diabetic men [52].…”
Section: The Acute-phase Response and Diabetic Complicationsmentioning
confidence: 99%